2004
DOI: 10.1080/0960310042000211623
|View full text |Cite
|
Sign up to set email alerts
|

Investment in information technology systems and other determinants of bank profitability in the UK

Abstract: This paper investigates whether investment in information technology systems affects bank profitability in the UK during the period 1976-1996. The results show that, when the other factors used in the literature are included, the number of automated teller machines installed by a bank has a positive impact on bank profitability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 9 publications
1
36
0
Order By: Relevance
“…Holden and El-Bannany [14] investigated whether IT investment affects bank profitability in the UK. The results showed that the number of ATM installed by a bank had a positive impact on bank profitability.…”
Section: Impact Of Atm Intensity On Banks' Cost Efficiencymentioning
confidence: 99%
“…Holden and El-Bannany [14] investigated whether IT investment affects bank profitability in the UK. The results showed that the number of ATM installed by a bank had a positive impact on bank profitability.…”
Section: Impact Of Atm Intensity On Banks' Cost Efficiencymentioning
confidence: 99%
“…2 One important exception isHolden and El-Bannany (2004), who look at the impact of ATM adoption and sharing on bank profits in the UK. Although they find a positive relationship between the number of ATMs and bank profit, they fail to find such evidence for a bank's membership in a shared ATM network.…”
mentioning
confidence: 98%
“…For example, Shawkey (1995), Daniel and Storey (1997), and Gupta (1998) show that investing in information technology results in cost savings and better services for customers, which should be reflected in increased bank profits. Holden and El-Bannany (2004) find that information technology system investment has a positive effect on bank profitability in retail banking. DeYoung (2005) argues that Internet-only banking success depends on attaining sufficient scale and strong management practices.…”
Section: Related Literaturementioning
confidence: 94%
“…However, these papers ignore the resource costs in technology choice, investment in human resource relative to information technology, incurred in intermediary operations. A growing body of research investigates the impact of human resource investment (e.g., Bartel, 2004;Lengnick-Hall, Lengnick-Hall, Andrade, & Drake, 2009), or information technology investment (e.g., Holden & El-Bannany, 2004;Keramati, Azadeh has on bank performance, the magnitude of these effects, and how they might differ with government capital injections under regulatory deposit insurance fund protection boils down to a question, one that we confront in this paper. 1 In retail banking, investment in human resource and information technology management are two key technology choice issues.…”
Section: Introductionmentioning
confidence: 99%